Reputational Implications for Partners After a Major Audit Failure: Evidence from China - He, Xianjie (Journal of business ethics, 2016)
We analyze whether audit partners suffered damage to their professional reputations with the demise of Zhongtianqin (ZTQ), formerly the largest audit firm in China, after an audit failure enabled a major client, Yinguangxia (YGX), to fraudulently exaggerate its earnings in a high-profile scandal resembling the Andersen–Enron events in the US. This involves evaluating whether the reputational damage sustained by partners implicated in the scandal spreads to other partners in the same audit firm. We isolate whether impaired reputation impedes partners who were not complicit in the ZTQ–YGX events from attracting new clients or keeping existing ones. Our evidence implies that the market shares of these partners fell after ZTQ’s collapse, supporting that guiltless partners’ reputations were tarnished. We also find that these partners are less likely to be employed by reputable audit firms. The clients of these partners tend to have lower earnings response coefficients, implying that investors downgrade the perceived quality of their audits. Moreover, compared to a matched sample, the former ZTQ partners tend to charge lower audit fees after the firm’s collapse. Finally, we exploit the unique structure of ZTQ to provide evidence consistent with the prediction that the former partners from the branch that handled the YGX audits experienced worse damage to their reputations. In a setting with minimal auditor discipline stemming from civil litigation, our results lend support to the intuition that partners’ reputation concerns motivate them to protect audit quality by closely monitoring other partners in the firm.